Electrode loaded with amorphous catalyst and preparation method and application thereof

By forming an aluminum-magnesium alloy transition layer and an amorphous catalyst layer on a metal nickel substrate, the problem of weak bonding force between the electrode and the amorphous catalyst is solved, and an electrode with high catalytic activity and stability is achieved, which is suitable for electrolytic hydrogen production technology.

CN119663349AActive Publication Date: 2025-03-21HUANENG YIMIN COAL POWER CO LTD +1

Patent Information

Application Number
CN202411717743.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the bonding force between the electrode and the amorphous catalyst is weak, resulting in low electrocatalytic activity and unstable.

Method used

Vacuum plasma spraying and cold spraying technology are used to form an aluminum-magnesium alloy transition layer and an amorphous catalyst layer on the metal nickel substrate, and the electrode structure is further optimized through heat treatment and alkali irrigation.

Benefits of technology

The binding force between the amorphous catalyst layer and the substrate is significantly improved, taking into account both catalytic activity and stability, and improving the catalytic performance of the electrode in HER and OER.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663349A_ABST
    Figure CN119663349A_ABST
Patent Text Reader

Abstract

The invention provides an electrode loaded with an amorphous catalyst as well as a preparation method and application of the electrode. The preparation method comprises the steps that aluminum metal powder and magnesium metal powder are subjected to first mixing, and mixed aluminum-magnesium powder is obtained; the mixed aluminum-magnesium powder is sprayed on the surface of at least one side of a metal nickel base material in a vacuum plasma spraying mode, and the metal nickel base material loaded with an aluminum-magnesium alloy transition layer is obtained; carrying out second mixing on the amorphous metal source and an auxiliary agent to obtain mixed amorphous powder; the mixed amorphous powder is sprayed on the surface of the side, away from the metal nickel base material, of the aluminum-magnesium alloy transition layer in a cold spraying mode, an amorphous catalyst layer is obtained, and then a first electrode is obtained; and sequentially carrying out heat treatment and alkaline leaching on the first electrode to obtain the electrode loaded with the amorphous catalyst. The aluminum-magnesium alloy transition layer is firstly prepared on the metal nickel base material, and then the amorphous catalyst layer is prepared through the cold spraying technology, so that the binding force between the amorphous catalyst layer and the base material is effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen production by electrolysis of water, and in particular to an electrode loaded with an amorphous catalyst, a preparation method and application thereof. Background Art

[0002] The shortage of fossil fuels and the resulting environmental pollution have triggered a strong interest in finding sustainable, clean and efficient energy sources to meet existing energy needs. Water electrolysis is an efficient and clean technology to obtain high-purity hydrogen, and using efficient electrocatalysts in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) to overcome thermodynamic barriers is an important way to improve economics.

[0003] Therefore, how to improve the catalytic activity and stability of electrode materials has become an important research direction for the industrialization of water electrolysis hydrogen production technology. Precious metal Pt-based catalysts have been used in OER and HER due to their good catalytic performance, but their high prices limit their large-scale application. Therefore, the development of new low-cost non-precious metal electrode materials with good catalytic performance has become a research hotspot.

[0004] Among many types of catalysts, amorphous materials can significantly increase the amount of active sites and optimize the adsorption and desorption of reactants due to their special structural characteristics of a large number of randomly oriented bonds and surface exposed defects. Many amorphous materials can be used for efficient electrocatalytic decomposition of water. However, since the structure of amorphous catalytic powders is often unstable, the crystallinity of the material will increase rapidly under high temperature conditions, resulting in the disappearance of its intrinsic special properties. Therefore, it is difficult to load amorphous materials on the surface of metal mesh with high bonding strength by traditional thermal spraying or high-temperature calcination, and further use them in actual water electrolysis hydrogen production.

[0005] Based on this, how to optimize the preparation method of electrodes used in the field of hydrogen production by water electrolysis so that they can load amorphous catalysts with high catalytic activity with high bonding strength, thereby exhibiting higher and more stable OER and HER catalytic activity, is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide an electrode loaded with an amorphous catalyst, a preparation method and application thereof, so as to solve the problem in the prior art that the bonding force between the electrode used for electrolysis of water to produce hydrogen and the amorphous catalyst is weak, resulting in low and unstable electrocatalytic activity.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing an electrode loaded with an amorphous catalyst, comprising: step S1, first mixing aluminum metal powder and magnesium metal powder to obtain mixed aluminum-magnesium powder; step S2, spraying the mixed aluminum-magnesium powder on at least one side surface of a metal nickel substrate by vacuum plasma spraying to obtain a metal nickel substrate loaded with an aluminum-magnesium alloy transition layer; step S3, second mixing an amorphous metal source and an auxiliary agent to obtain a mixed amorphous powder; step S4, spraying the mixed amorphous powder on the side surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate by cold spraying to obtain an amorphous catalyst layer, and then obtaining a first electrode; step S5, sequentially heat treating and alkali immersing the first electrode to obtain an electrode loaded with an amorphous catalyst; the amorphous metal source comprises a first amorphous metal source and a second amorphous metal source, and the weight ratio of the first amorphous metal source to the second amorphous metal source is 1: (1 to 2.5); the first amorphous metal source is a nickel source, and the second amorphous source is a precious metal source and / or one or more transition metal sources other than a nickel source.

[0008] Furthermore, the second amorphous source is one or more metal sources with atomic numbers of 22 to 30 other than the nickel source; preferably, the second amorphous metal source is selected from one or more of a cobalt metal source, an iron metal source and a copper metal source; more preferably, the second amorphous metal source is a cobalt metal source, an iron metal source and a copper metal source, and the weight ratio of the cobalt metal source, the iron metal source and the copper metal source is 1:(0.4 to 0.6):1; further preferably, the first amorphous metal source and the second amorphous metal source are each independently one or more of nitrates, sulfates, acetates, acetylacetonates and chlorides.

[0009] Further, in step S1, the weight ratio of aluminum metal powder to magnesium metal powder is 1:(0.1-10), preferably 1:(1-2); preferably, the mesh sizes of aluminum metal powder and magnesium metal powder are independently 100-500 mesh; more preferably, the first mixing method is ball milling, and the rotation speed of the ball mill is 150r / min-500r / min, the time is 0.5h-10h, and the ball milling beads are 10mm-30mm zircon beads; further preferably, the dispersion liquid used for ball milling is ethanol, and the ratio of the weight of ethanol to the sum of the weight of the aluminum metal powder and the magnesium metal powder is 1:(6-12).

[0010] Further, in step S2, the power of vacuum plasma spraying is 20 kW to 25 kW, the powder feeding rate is 10 g / min to 100 g / min, the distance between the nozzle and the metal nickel substrate is 25 cm to 80 cm, and the movement rate of the spray gun is 50 cm / s to 80 cm / s; preferably, in vacuum plasma spraying, the process gas for generating plasma is H 2 / Ar mixed gas, and H 2The total flow rate of the H / Ar mixed gas is 8 L / min to 15 L / min; more preferably, the H 2 In the mixed gas of H / Ar, 2 The volume ratio to Ar is 1:(2~10).

[0011] Further, in step S3, the molar ratio of the amorphous metal source and the auxiliary agent is (0.2-10):1, preferably (2.0-6.0):1; preferably, the auxiliary agent is selected from one or more of sodium borohydride, thiourea and sodium hypophosphite, preferably sodium borohydride; more preferably, the second mixing method is ball milling, and the ball milling speed is 150r / min-500r / min, the time is 0.5h-10h, and the ball milling beads are 10mm-30mm zircon beads; further preferably, the dispersion liquid used for ball milling is ethanol, and the ratio of the weight of ethanol to the sum of the weight of the amorphous metal source and the auxiliary agent is 1:(4-8).

[0012] Further, in step S4, the pressure of cold spraying is 1MPa-10MPa, the temperature is 400℃-600℃, the distance between the nozzle and the aluminum-magnesium alloy transition layer is 10cm-60cm, the powder feeding rate is 10g / min-100g / min, and the movement rate of the spray gun is 20cm / s-60cm / s; preferably, the propelling gas used for cold spraying is N 2 / He mixed gas, and N 2 In the mixed gas of N / He, 2 The volume ratio of He is 1:(0.1 to 10), and more preferably 1:(4 to 5).

[0013] Further, in step S5, the heat treatment temperature is 250°C to 350°C, the time is 0.5 to 5h, and the atmosphere used is selected from one or more of air atmosphere, vacuum atmosphere, nitrogen atmosphere, argon atmosphere, hydrogen atmosphere and helium atmosphere; and / or, the mass concentration of alkali solution used for alkali leaching is 10wt% to 30wt%, and the alkali leaching is carried out at 25°C to 80°C for 6h to 24h.

[0014] The second aspect of the present invention provides an electrode loaded with an amorphous catalyst, comprising a metal nickel substrate. The electrode loaded with an amorphous catalyst is prepared by the above-mentioned method for preparing an electrode loaded with an amorphous catalyst.

[0015] Furthermore, the electrode loaded with an amorphous catalyst also includes an alloy transition layer and an amorphous catalyst layer loaded on at least one side surface of a metal nickel substrate, and the alloy transition layer is arranged in contact with the metal nickel substrate, and the amorphous catalyst layer is arranged on the side surface of the alloy transition layer away from the metal nickel substrate; preferably, the thickness of the amorphous catalyst layer is 10μm to 150μm, more preferably 40μm to 50μm.

[0016] The third aspect of the present invention provides an application of the above-mentioned electrode loaded with an amorphous catalyst as an electrode in a water electrolysis hydrogen production system, wherein the water electrolysis hydrogen production system is an alkaline water electrolysis system or an anion exchange membrane water electrolysis system; preferably, the water electrolysis hydrogen production system is an alkaline water electrolysis system, and the electrode loaded with an amorphous catalyst is used as an oxygen evolution working electrode and / or a hydrogen evolution working electrode in the alkaline water electrolysis system; and / or, the water electrolysis hydrogen production system is an anion exchange membrane water electrolysis system, and the electrode loaded with an amorphous catalyst is used as a self-supporting oxygen evolution electrode and / or a self-supporting hydrogen evolution electrode in the anion exchange membrane water electrolysis system.

[0017] By applying the technical solution of the present invention, an aluminum-magnesium alloy transition layer is first prepared on a metal nickel substrate, and then an amorphous catalyst layer is prepared by cold spraying technology, thereby effectively enhancing the bonding strength between the amorphous catalyst layer and the substrate, taking into account the bonding between the amorphous catalyst and the metal nickel substrate, while retaining the unique high catalytic activity of the amorphous structure, thereby significantly improving the catalytic activity and cycle stability of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 This is the SEM morphology characterization result of the electrode loaded with amorphous catalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] As described in the background technology, there is a weak bonding force between the electrode used for electrolysis of water to produce hydrogen in the prior art and the amorphous catalyst, which leads to the problem of low electrocatalytic activity and instability. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing an electrode loaded with an amorphous catalyst, comprising: step S1, first mixing aluminum metal powder and magnesium metal powder to obtain a mixed aluminum-magnesium powder; step S2, using vacuum plasma spraying to spray the mixed aluminum-magnesium powder on at least one side of the surface of a metal nickel substrate to obtain a metal nickel substrate loaded with an aluminum-magnesium alloy transition layer; step S3, second mixing an amorphous metal source and an additive to obtain a mixed amorphous powder; step S4, using cold spraying , spraying the mixed amorphous powder onto the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate to obtain an amorphous catalyst layer, and then obtaining a first electrode; step S5, sequentially heat treating and alkali immersing the first electrode to obtain an electrode loaded with an amorphous catalyst; the amorphous metal source includes a first amorphous metal source and a second amorphous metal source, and the weight ratio of the first amorphous metal source to the second amorphous metal source is 1: (1 to 2.5); the first amorphous metal source is a nickel source, and the second amorphous source is one or more of a precious metal source and / or a transition metal source other than a nickel source.

[0022] The present invention selects a low-melting aluminum-magnesium alloy as a connecting transition layer between an amorphous catalyst and a metal nickel substrate, first forms a low-melting aluminum-magnesium alloy transition layer by vacuum plasma spraying, then prepares a nickel-based amorphous catalyst, and uses a high-pressure cold spraying process to embed the amorphous catalyst in the transition layer alloy surface by high-speed impact of the amorphous catalyst on the low-melting aluminum-magnesium alloy transition layer. The instantaneous high temperature generated only crystallizes the interface portion where the amorphous compound contacts the aluminum-magnesium alloy, which is beneficial to the combination of the catalyst and the metal nickel substrate. At the same time, the remaining main body of the catalyst still maintains a high degree of amorphous state, and its related special catalytic properties are retained. The electrode loaded with an amorphous catalyst thus obtained not only takes into account the binding property with the substrate, but also retains the unique catalytic performance of the amorphous catalyst structure, and then exhibits excellent catalytic activity and stability in both HER and OER.

[0023] Specifically, in the process of forming the transition layer of aluminum-magnesium alloy, compared with traditional powder metallurgy methods such as coating and sintering, vacuum plasma spraying can prevent aluminum-magnesium alloy from being oxidized during hot spraying or sintering, resulting in the formation of a brittle oxide coating on the electrode surface, and prevent it from peeling off during subsequent applications, thereby effectively improving the bonding strength between the aluminum-magnesium alloy as a transition coating and the substrate, so as to further construct a highly stable amorphous coating on the surface. The use of cold spraying to embed the amorphous catalyst on the surface of the transition layer alloy can rely on the high pressure conditions during the cold spraying process to ensure that the amorphous catalyst achieves crystallization at the interface and the main part remains amorphous, thereby taking into account high bonding strength and high catalytic activity. After that, the stress caused by mechanical impact is eliminated by heat treatment, and then the aluminum element in the aluminum-magnesium alloy is removed by alkaline leaching to correct the structural damage, catalytic activity and stability caused by the high metal activity of aluminum-based materials and their easy solubility in acidic or alkaline electrolytes.

[0024] In particular, a second amorphous metal source is introduced on the basis of a nickel-based amorphous catalyst, and the weight ratio of the first amorphous metal source, that is, the nickel source, to the second amorphous metal source is controlled to be 1: (1 to 2.5). The addition of another heterogeneous metal atom in a specific proportion can reduce the orderliness of the lattice arrangement, thereby increasing the degree of crystal disorder of the material, and ultimately strengthening the catalytic performance of the formed amorphous material. As for the type of the second amorphous metal source, since nickel itself as the first amorphous metal source belongs to a transition metal, the inventors have selected transition metals other than nickel and precious metals with excellent intrinsic catalytic performance as the second amorphous metal source through a large number of experiments to cooperate with it, thereby more significantly improving the electrocatalytic activity of the electrode loaded with the amorphous catalyst.

[0025] In practical applications, the noble metal source includes the noble metals ruthenium, rhodium, palladium, osmium, iridium and platinum. The transition metal source other than the nickel source includes the transition metals titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc.

[0026] In addition, the advantages of the present invention are simple preparation process, low cost of raw materials, short preparation cycle, and can achieve large-scale preparation with equal proportions, which provides a useful reference for the industrial preparation and application of amorphous catalyst electrodes. Compared with the powdered amorphous catalyst prepared by traditional methods, the electrode prepared by the present invention based on the amorphous catalyst has catalytic performance and structural strength that meet the requirements of electrodes used for electrolysis of water in industrial applications, providing a new choice for commercial electrolytic cell electrodes.

[0027] In several typical embodiments, in order to more significantly optimize the electronic structure of the obtained amorphous catalyst, thereby comprehensively improving the catalytic activity of HER and OER, the second amorphous source is preferably one or more metal sources with atomic numbers of 22 to 30 other than the nickel source.

[0028] In a more typical embodiment, the second amorphous metal source is selected from one or more of a cobalt metal source, an iron metal source, and a copper metal source. This is because the d orbital electron configuration of nickel in the divalent state is 3d 8 , the d orbital electron configuration of the divalent cobalt source is 3d 7 , the d orbital electron configuration of the trivalent iron source is 3d 5 , the d orbital electron configuration of the divalent copper source is 3d 9 , which all belong to the metals on the left side of the transition system with an unfilled or half-filled d orbital in Engel Brewer's valence bond theory. When metal sources with this special d orbital electronic structure are doped and coordinated to form an amorphous compound, the d orbital electrons of the above-mentioned metal ions can exchange to form an electron cloud, split the energy level, and change the energy band structure, thereby optimizing their overall electronic properties. This in turn enhances the interaction between them, thereby enhancing the adsorption of water molecules by the formed amorphous catalyst layer, and making H + and OH - The reaction with d-orbital electrons is easier to occur, and finally the HER and OER catalytic activities are comprehensively improved. In particular, in the OER process, it is further preferred that the second amorphous metal source contains a cobalt metal source, an iron metal source and a copper metal source at the same time, and the weight ratio of the cobalt metal source, the iron metal source and the copper metal source is 1: (0.4-0.6): 1. Since the above-mentioned transition metals with unfilled d-orbitals are either in tetrahedral coordination or in octahedral coordination, when they are in such a precise synergistic doping ratio, the metals can cooperate with each other to increase the number of octahedral sites in the catalytic process, so it is easier to construct oxygen vacancies and optimize the H 2 The adsorption of O promotes the occurrence of OER, and the catalytic activity is particularly significant.

[0029] Further preferably, the first amorphous metal source and the second amorphous metal source are independently one or more of nitrate, sulfate, acetate, acetylacetonate and chloride. The above salts, as carriers of the above amorphous metal sources, can not only promote the formation of the amorphous catalyst layer, but also further optimize the performance of the catalyst through its decomposition products, so that the obtained electrode exhibits more superior catalytic activity.

[0030] In the preparation process of the mixed aluminum-magnesium powder, in order to obtain an aluminum-magnesium alloy transition layer with better bonding and conductivity, the weight ratio of the aluminum metal powder to the magnesium metal powder in step S1 is preferably 1: (0.1-10), preferably 1: (1-2). The aluminum-magnesium alloy transition layer obtained by mixing and spraying at this weight ratio can provide a more stable bonding effect between the amorphous catalyst layer and the metal nickel matrix, thereby improving the existence stability of the amorphous catalyst layer and the overall catalytic performance of the electrode. It is preferred that the mesh size of the aluminum metal powder and the magnesium metal powder is independently 100 mesh to 500 mesh, which can ensure that the aluminum-magnesium alloy transition layer formed during the vacuum plasma spraying process has better uniformity and density, thereby improving the stability and catalytic efficiency of the electrode.

[0031] Furthermore, for the mixing process of aluminum-magnesium powder, in order to improve the uniformity of the subsequent aluminum-magnesium alloy transition layer and promote the optimization of the microstructure, so as to make the combination of the amorphous catalyst layer and the metal nickel substrate more stable, it is preferred that the first mixing method is ball milling, and the rotation speed of the ball milling is 150r / min~500r / min, preferably 250±50r / min; the time is 0.5h~10h, preferably 2h~3h; the ball milling beads are 10mm~30mm zircon beads. More preferably, the dispersion liquid used for ball milling is ethanol, and the ratio of the weight of ethanol to the weight of the aluminum metal powder and the magnesium metal powder is 1: (6~12), so as to improve the dispersion uniformity of the mixed ball milling system in the first mixing process, make the particle size of the obtained mixed aluminum-magnesium powder more uniform, and then optimize the microstructure of the aluminum-magnesium alloy transition layer and improve the existence stability of the amorphous catalyst layer.

[0032] In several typical embodiments, in order to further optimize the structure of the obtained aluminum-magnesium alloy transition layer and reduce the formation of defects, step S1 also includes drying the obtained mixed aluminum-magnesium powder, and the preferred drying method is vacuum drying, the temperature is 25°C to 60°C, more preferably 50°C to 60°C, and the time is 0.5 to 24h, more preferably 12±2h.

[0033] In the process of forming the aluminum-magnesium alloy transition layer, that is, in the process of vacuum plasma spraying, the inventors have optimized the vacuum plasma spraying power to be 20kW to 25kW after a large number of experiments; the powder feeding rate is 10g / min to 100g / min, and more preferably 50±10g / min; the distance between the nozzle and the metal nickel substrate is 25cm to 80cm, and more preferably 60±10cm; the spray gun moving rate is 50cm / s to 80cm / s, and more preferably 50cm / s to 60cm / s. These spraying parameters can promote the uniformity and density of the aluminum-magnesium alloy transition layer obtained by spraying, and also make the subsequent amorphous catalyst layer more tightly bonded thereon, thereby more effectively improving the bonding force between the amorphous catalyst layer and the metal nickel substrate, and optimizing the overall catalytic activity and cycle stability of the resulting electrode.

[0034] In the process of spraying, in order to better protect the mixed aluminum-magnesium powder from oxidation, so as to make the microstructure of the aluminum-magnesium alloy transition layer denser, with fewer impurities, and more convenient for subsequent alkaline leaching to remove unstable aluminum, so as to obtain an electrode with higher catalytic activity and stability, it is preferred that the process gas for generating plasma in vacuum plasma spraying is H 2 / Ar mixed gas, and H 2 The total flow rate of the H / Ar mixed gas is 8 L / min to 15 L / min. In several typical embodiments, H 2 H in the mixed gas of Ar 2 The volume ratio of H to Ar is 1:(2~10). 2 The Ar / Ar mixed gas can make the formed aluminum-magnesium alloy transition layer more uniform and dense, while effectively utilizing the reducing effect of hydrogen, further optimizing the microstructure of the resulting transition layer, reducing impurities therein, and ultimately improving the overall performance of the resulting electrode.

[0035] In several typical embodiments, preferably, the weight of the metal nickel substrate is 100%, and the loading amount of the aluminum-magnesium alloy transition layer formed by vacuum plasma spraying is 100 g / m 2 ~120g / m 2 The loading amount screening in this range can make the amorphous catalyst layer subsequently loaded thereon better combined with it, and also make the final alkaline leaching process more perfect for the removal of aluminum in the aluminum-magnesium alloy transition layer, thus obtaining an electrode with higher catalytic activity and cycle stability.

[0036] In the preparation process of mixed amorphous powder, the molar ratio of amorphous metal source and auxiliary agent is preferably (0.2-10):1, more preferably (2.0-6.0):1, so as to better play the role of auxiliary agent, further optimize the electronic structure, chemical structure and microscopic morphology of the obtained mixed amorphous powder, i.e., the amorphous catalyst precursor, and optimize its catalytic activity and cycle stability in the electrode system.

[0037] In several typical embodiments, the preferred auxiliary agent is selected from one or more of sodium borohydride, thiourea and sodium hypophosphite, more preferably sodium borohydride. This is because sodium borohydride has strong reducibility at room temperature, and can more quickly reduce transition metal ion salts to metals, resulting in rapid nucleation and growth of materials in the liquid phase, inhibiting the growth process of the ordered structure, so that a highly amorphous structure can be formed, and multiple elements therein are uniformly and disorderly arranged, which is ultimately conducive to the in-situ adaptive reconstruction of the amorphous structure into a catalytically active phase in the electrochemical reaction. It is further preferred that the second mixing method is ball milling, and the ball milling speed is 150r / min~500r / min, more preferably 150r / min~200r / min; the time is 0.5h~10h, more preferably 0.5h~1h; the ball milling beads are 10mm~30mm zircon beads. The above ball milling conditions can improve the mixing uniformity of the amorphous metal source and the auxiliary agent, and obtain an amorphous catalyst with higher structural stability and integrity. At the same time, in the subsequent cold spraying process, the part of the amorphous catalyst that collides with the surface of the aluminum-magnesium alloy transition layer can be more fully crystallized, thereby improving its bonding strength, thereby improving its activity and stability in the catalytic process. In several more typical embodiments, the dispersion liquid used for ball milling is preferably ethanol, and the ratio of the weight of ethanol to the weight of the amorphous metal source and the auxiliary agent is 1: (4-8), so as to further improve the mixing uniformity of the amorphous metal source and the auxiliary agent, optimize the microstructure of the formed amorphous catalyst layer, and improve its bonding strength.

[0038] In order to reduce the moisture content of the obtained mixed amorphous powder, facilitate subsequent cold spraying, and reduce the problems of reduced catalytic activity and instability caused by the generation of impurities, after obtaining the mixed amorphous powder, step S3 preferably also includes vacuum drying the mixed amorphous powder, and the vacuum drying temperature is 25°C to 60°C, more preferably 55°C to 60°C; the time is 0.5 to 24h, more preferably 6±1h.

[0039] In the process of cold spraying to form an amorphous catalyst layer in step S4, the inventors have optimized the cold spraying pressure to be 1MPa to 10MPa, more preferably 4MPa to 5MPa, after a large number of experiments; the temperature is 400℃ to 600℃; the distance between the nozzle and the aluminum-magnesium alloy transition layer is 10cm to 60cm, more preferably 50cm to 60cm; the powder feeding rate is 10g / min to 100g / min, more preferably 25±5g / min; the spray gun movement rate is 20cm / s to 60cm / s, more preferably 40±5cm / s. The above spraying parameters can crystallize the amorphous mixed powder that collides with the aluminum-magnesium alloy transition layer at high speed, improve the bonding, and at the same time keep the majority of the catalyst powder in the formed amorphous catalyst layer in an amorphous state, so that the obtained electrode loaded with amorphous catalyst can take into account both high catalytic activity and cycle stability. Furthermore, the selection of the above parameters can also help improve the microscopic uniformity and density of the formed amorphous catalyst layer itself, thereby more significantly improving the catalytic activity and stability of the final electrode.

[0040] In order to more effectively prevent the cold-sprayed amorphous material from impacting the nickel-magnesium coating and causing it to oxidize to form a ceramic oxide layer, so as to improve the bonding strength between the amorphous material and the nickel-magnesium coating substrate, the propulsion gas used for cold spraying is preferably N 2 / He mixed gas, and N 2 In the mixed gas of N / He, 2 The volume ratio of He is 1:(0.1 to 10), and more preferably 1:(4 to 5).

[0041] In several typical embodiments, in step S5, the temperature of the heat treatment is preferably 250°C to 350°C, the time is 0.5 to 5h, and the atmosphere used is selected from one or more of air atmosphere, vacuum atmosphere, nitrogen atmosphere, argon atmosphere, hydrogen atmosphere and helium atmosphere. The above-mentioned heat treatment conditions can better eliminate the internal stress generated by the amorphous catalyst layer during the cold spraying process, thereby more significantly optimizing its microstructure and improving its catalytic activity and stability. In order to more thoroughly remove the aluminum in the aluminum-magnesium alloy transition layer formed in step S2, and thus better avoid the problem of catalytic deactivation caused by alkali dissolution / acid dissolution that may occur in aluminum. At the same time, in order to more effectively remove impurities on the surface of the final electrode, optimize its surface state, and improve its catalytic activity and stability, the mass concentration of the alkali solution used for alkali leaching is preferably 10wt% to 30wt%, and the alkali leaching is carried out at 25°C to 80°C for 6h to 24h; more preferably, the alkali leaching is carried out at 25°C to 40°C for 6h to 10h.

[0042] Furthermore, based on the above alkali leaching conditions, the alkali solution preferably also includes a corrosion inhibitor with a mass concentration of 5wt% to 6wt%, so as to better control the process of removing aluminum and impurities by alkali leaching and obtain an electrode with better comprehensive performance. More preferably, the corrosion inhibitor is potassium sodium tartrate.

[0043] The second aspect of the present invention provides an electrode loaded with an amorphous catalyst, comprising a metal nickel substrate, wherein the electrode loaded with an amorphous catalyst is prepared by the above-mentioned method for preparing an electrode loaded with an amorphous catalyst. The obtained electrode has an amorphous catalyst layer with high catalytic activity and strong binding force, so it can exhibit high catalytic activity and cycle stability in a variety of electrocatalytic reactions.

[0044] Furthermore, the electrode loaded with an amorphous catalyst also includes an alloy transition layer and an amorphous catalyst layer loaded on at least one side of the surface of the metal nickel substrate, and the alloy transition layer is arranged in contact with the metal nickel substrate, and the amorphous catalyst layer is arranged on the side of the alloy transition layer away from the metal nickel substrate. The above structural design uses the alloy transition layer with good conductivity as the intermediate layer between the catalyst layer and the substrate layer, which not only significantly enhances the bonding force between the amorphous catalyst layer and the substrate, but also well protects the conductivity of the electrode, thereby enabling the obtained electrode to have both high catalytic activity and excellent stability.

[0045] In several preferred embodiments, in order to better coordinate the mechanical properties of each layer with the metal nickel substrate, make them more tightly combined, and have higher structural stability during the electrocatalytic process, the thickness of the amorphous catalyst layer is 10μm to 150μm, and more preferably 40μm to 50μm.

[0046] The third aspect of the present invention provides an application of the above-mentioned electrode loaded with an amorphous catalyst as an electrode in a water electrolysis hydrogen production system, and the water electrolysis hydrogen production system is an alkaline water electrolysis system or an anion exchange membrane water electrolysis system. The electrode obtained by the present invention not only has high catalytic activity, but also can be applied to a variety of water electrolysis catalytic systems, including high pressure, high temperature and different pH conditions. In practical applications, this electrode can significantly reduce the cost of water electrolysis hydrogen production, improve the yield and purity of hydrogen, so as to better provide support for the sustainable production of hydrogen energy, and lay a solid foundation for the widespread application and sustainable development of hydrogen energy.

[0047] In a typical embodiment, the electrolysis water hydrogen production system is an alkaline electrolysis water system, and the electrode loaded with an amorphous catalyst is used as an oxygen evolution working electrode and / or a hydrogen evolution working electrode in the alkaline electrolysis water system. And, in another typical embodiment, the electrolysis water hydrogen production system is an anion exchange membrane electrolysis water system, and the electrode loaded with an amorphous catalyst is used as a self-supporting oxygen evolution electrode and / or a self-supporting hydrogen evolution electrode in the anion exchange membrane electrolysis water system. In other words, the electrode loaded with an amorphous catalyst prepared by the preparation method provided by the present invention exhibits special and excellent HER / OER bifunctional catalytic properties due to the above-mentioned specific structure, and it exhibits excellent catalytic performance both in the alkaline electrolysis water system and in the anion exchange membrane electrolysis water system.

[0048] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0049] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0050] Example 1

[0051] A method for preparing an electrode loaded with an amorphous catalyst:

[0052] (1) 100 g of aluminum metal powder with a mesh size of 325, 200 g of magnesium metal powder with a mesh size of 325 (the weight ratio of the aluminum metal powder to the magnesium metal powder is 1:2) and 50 g of ethanol are mixed by ball milling (i.e., the weight ratio of ethanol to the sum of the two metal powders is 1:6), the ball milling speed is 250 r / min, the time is 2 h, and 20 mm zircon beads are selected as ball milling beads. Then, the mixed powder is taken out and vacuum dried at a temperature of 60° C. for 12 h to obtain a mixed aluminum-magnesium powder;

[0053] (2) A nickel felt with a porosity of 80% was used as a metal nickel substrate, and the mixed aluminum-magnesium powder was clad on the metal nickel substrate by vacuum plasma spraying. The power of the vacuum plasma spraying was 25 kW, and the process gas for generating the plasma was H 2 / Ar mixed gas (H 2 :AR=1:2, volume ratio), the total flow rate is 8L / min, the powder feeding rate of the mixed aluminum-magnesium powder is 50g / min, the distance between the nozzle and the metal nickel substrate is 60cm, the movement rate of the spray gun is 50cm / s, and the aluminum-magnesium alloy transition layer is obtained, and its loading amount on the surface of the metal nickel substrate is 100g / m 2 ;

[0054] (3) Nickel chloride is used as the first amorphous metal source, and cobalt chloride is used as the second amorphous metal source. 50 g of cobalt chloride, 50 g of nickel chloride (the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:1), 25 g of ethanol and 5 g of sodium borohydride are mixed and then ball milled to prepare an amorphous catalyst (i.e., the molar ratio of the amorphous metal source to the auxiliary agent is 5.83:1, and the weight ratio of ethanol to the amorphous metal source and the auxiliary agent is 1:4.2). The ball milling speed is 150 rpm and the time is 1 h. 20 mm zircon beads are selected. Then, the mixed powder is taken out and vacuum dried at 60° C. for 6 h to obtain a mixed amorphous powder.

[0055] (4) The mixed amorphous powder is sprayed on the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate by high-pressure cold spraying. The propelling gas for high-pressure cold spraying is N 2 / He mixed gas (N 2 :He=1:4, volume ratio), pressure is 4MPa, cold spray temperature is 400℃, distance between nozzle and aluminum-magnesium alloy transition layer is 50cm, powder feeding rate is 25g / min, spray gun moving rate is 40cm / s, and an amorphous catalyst layer with a thickness of 40μm is obtained, thereby obtaining a first electrode;

[0056] (5) The stress generated by mechanical impact during the cold spraying process is eliminated by low-temperature annealing heat treatment. The annealing heat treatment temperature is 250°C, the time is 0.5h, and the atmosphere is a nitrogen atmosphere; then the aluminum element in the aluminum-magnesium alloy is removed by alkali leaching to obtain a nickel-cobalt amorphous electrode. The alkali solution required for the alkali leaching treatment is a 10wt% potassium hydroxide solution. The treatment temperature is 25°C and the treatment time is 6h. 5wt% potassium sodium tartrate is also added to the alkali solution as a corrosion inhibitor, and finally an electrode loaded with an amorphous catalyst is obtained.

[0057] The SEM morphology of the obtained electrode loaded with amorphous catalyst is shown in Figure 1 .

[0058] Example 2

[0059] A method for preparing an electrode loaded with an amorphous catalyst:

[0060] The only difference between this embodiment and embodiment 1 is that in step (3), the second amorphous metal source is changed to ferric chloride, and 50 g of ferric chloride, 50 g of nickel chloride, 25 g of ethanol and 5 g of sodium borohydride are mixed and then ball milled to prepare an amorphous catalyst.

[0061] At this time, the molar ratio of the amorphous metal source to the auxiliary agent is 5.24:1.

[0062] Example 3

[0063] A method for preparing an electrode loaded with an amorphous catalyst:

[0064] The only difference between this embodiment and embodiment 1 is that in step (3), the second amorphous metal source is changed to ferric chloride, copper chloride and cobalt chloride, and 50g of copper chloride, 25g of ferric chloride, 50g of cobalt chloride, 50g of nickel chloride, 25g of ethanol and 20g of sodium borohydride are mixed and then ball milled to prepare an amorphous catalyst.

[0065] At this time, the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:2.5; the molar ratio of the amorphous metal source and the auxiliary agent is 2.45:1; and the weight ratio of ethanol to the amorphous metal source and the auxiliary agent is 1:7.8.

[0066] And, in the second amorphous metal source, the weight ratio of the cobalt metal source, the iron metal source and the copper metal source is 1:0.5:1.

[0067] Example 4

[0068] A method for preparing an electrode loaded with an amorphous catalyst:

[0069] The only difference between this embodiment and embodiment 1 is that in step (3), the second amorphous metal source is changed to platinum chloride, and 50 g of platinum chloride, 50 g of nickel chloride, 25 g of ethanol and 5 g of sodium borohydride are mixed and then ball milled to prepare an amorphous catalyst.

[0070] At this time, the molar ratio of the amorphous metal source to the auxiliary agent is 4.05:1.

[0071] Example 5

[0072] A method for preparing an electrode loaded with an amorphous catalyst:

[0073] The only difference between this embodiment and embodiment 1 is that in step (3), the second amorphous metal source is changed to ferric chloride, copper chloride and cobalt chloride, and 41.6 g of copper chloride, 41.6 g of ferric chloride, 41.7 g of cobalt chloride, 50 g of nickel chloride, 25 g of ethanol and 20 g of sodium borohydride are mixed and then ball milled to prepare an amorphous catalyst.

[0074] At this time, the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:2.5; and the molar ratio of the amorphous metal source to the auxiliary agent is 2.28:1.

[0075] The weight ratio of ethanol to the amorphous metal source and the auxiliary agent is 1:7.8.

[0076] And, in the second amorphous metal source, the weight ratio of the cobalt metal source, the iron metal source and the copper metal source is 1:1:1.

[0077] Example 6

[0078] A method for preparing an electrode loaded with an amorphous catalyst:

[0079] The difference between this embodiment and embodiment 1 is only in step (1), specifically:

[0080] 60g of aluminum metal powder with a mesh size of 100 mesh, 240g of magnesium metal powder with a mesh size of 100 mesh (the weight ratio of aluminum metal powder to magnesium metal powder is 1:4) and 150g of ethanol are mixed by ball milling (that is, the ratio of ethanol to the sum of the weights of the two metal powders is 1:2), the ball milling speed is 100r / min, the time is 12h, 20mm zircon beads are selected as ball milling beads, and then the mixed powder is taken out and vacuum dried at 20°C for 30h to obtain mixed aluminum-magnesium powder.

[0081] Example 7

[0082] A method for preparing an electrode loaded with an amorphous catalyst:

[0083] The difference between this embodiment and embodiment 1 is only in step (1), specifically:

[0084] 200g of aluminum metal powder with a mesh size of 100 mesh, 100g of magnesium metal powder with a mesh size of 100 mesh (the weight ratio of aluminum metal powder to magnesium metal powder is 1:0.5) and 20g of ethanol are mixed by ball milling (that is, the ratio of ethanol to the sum of the weights of the two metal powders is 1:15), the ball milling speed is 600r / min, the time is 0.2h, 20mm zircon beads are selected as ball milling beads, and then the mixed powder is taken out and vacuum dried at 80°C for 0.2h to obtain mixed aluminum-magnesium powder.

[0085] Example 8

[0086] A method for preparing an electrode loaded with an amorphous catalyst:

[0087] The difference between this embodiment and embodiment 1 is only in step (2), specifically:

[0088] The nickel felt with a porosity of 80% was used as the metal nickel substrate, and the mixed aluminum-magnesium powder was clad on the metal nickel substrate by vacuum plasma spraying. The power of the vacuum plasma spraying was 10 kW, and the process gas for generating the plasma was H 2 / Ar mixed gas (H 2 :AR=1:1, volume ratio), the total flow rate is 6L / min, the powder feeding rate of the mixed aluminum-magnesium powder is 150g / min, the distance between the nozzle and the metal nickel substrate is 15cm, the movement rate of the spray gun is 40cm / s, and the aluminum-magnesium alloy transition layer is obtained, and its loading amount on the surface of the metal nickel substrate is 128g / m 2 .

[0089] Example 9

[0090] A method for preparing an electrode loaded with an amorphous catalyst:

[0091] The difference between this embodiment and embodiment 1 is only in step (2), specifically:

[0092] The nickel felt with a porosity of 80% was used as the metal nickel substrate, and the mixed aluminum-magnesium powder was clad on the metal nickel substrate by vacuum plasma spraying. The power of the vacuum plasma spraying was 40 kW, and the process gas for generating the plasma was H 2 / Ar mixed gas (H 2 :AR=1:15, volume ratio), the total flow rate is 18L / min, the powder feeding rate of the mixed aluminum-magnesium powder is 5g / min, the distance between the nozzle and the metal nickel substrate is 100cm, the movement rate of the spray gun is 100cm / s, and the aluminum-magnesium alloy transition layer is obtained, and its loading amount on the surface of the metal nickel substrate is 86g / m 2 .

[0093] Example 10

[0094] A method for preparing an electrode loaded with an amorphous catalyst:

[0095] The difference between this embodiment and embodiment 1 is only in step (3), specifically:

[0096] Nickel chloride is used as the first amorphous metal source, and cobalt chloride is used as the second amorphous metal source. 50g of cobalt chloride, 50g of nickel chloride (the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:1), 65g of ethanol and 29.2g of sodium borohydride are mixed and then an amorphous catalyst is prepared by ball milling (that is, the molar ratio of the amorphous metal source and the auxiliary agent is 1:1, and the weight ratio of ethanol to the amorphous metal source and the auxiliary agent is 1:2). The ball milling speed is 100 rpm, the time is 12h, 20mm zircon beads are selected, and then the mixed powder is taken out and vacuum dried at 20°C for 30h to obtain a mixed amorphous powder.

[0097] Embodiment 11

[0098] A method for preparing an electrode loaded with an amorphous catalyst:

[0099] The difference between this embodiment and embodiment 1 is only in step (3), specifically:

[0100] Nickel chloride is used as the first amorphous metal source, and cobalt chloride is used as the second amorphous metal source. 50g of cobalt chloride, 50g of nickel chloride (the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:1), 10g of ethanol and 3.6g of sodium borohydride are mixed and then an amorphous catalyst is prepared by ball milling (that is, the molar ratio of the amorphous metal source and the auxiliary agent is 8:1, and the weight ratio of ethanol to the amorphous metal source and the auxiliary agent is 1:10.4). The ball milling speed is 600 rpm, the time is 0.2h, 20mm zircon beads are selected, and then the mixed powder is taken out and vacuum dried at 80°C for 0.2h to obtain a mixed amorphous powder.

[0101] Example 12

[0102] A method for preparing an electrode loaded with an amorphous catalyst:

[0103] The difference between this embodiment and embodiment 1 is only in step (4), specifically:

[0104] The mixed amorphous powder is sprayed on the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate by high-pressure cold spraying. The propelling gas for high-pressure cold spraying is N 2 / He mixed gas (N 2 :He=1:2, volume ratio), the pressure is 0.5MPa, the cold spraying temperature is 200℃, the distance between the nozzle and the aluminum-magnesium alloy transition layer is 5cm, the powder feeding rate is 120g / min, the spray gun moving rate is 10cm / s, and an amorphous catalyst layer with a thickness of 55μm is obtained, thereby obtaining the first electrode.

[0105] Embodiment 13

[0106] A method for preparing an electrode loaded with an amorphous catalyst:

[0107] The difference between this embodiment and embodiment 1 is only in step (4), specifically:

[0108] The mixed amorphous powder is sprayed on the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate by high-pressure cold spraying. The propelling gas for high-pressure cold spraying is N 2 / He mixed gas (N 2 :He=1:8, volume ratio), the pressure is 12MPa, the cold spraying temperature is 800℃, the distance between the nozzle and the aluminum-magnesium alloy transition layer is 70cm, the powder feeding rate is 5g / min, the spray gun moving rate is 80cm / s, and an amorphous catalyst layer with a thickness of 34μm is obtained, thereby obtaining the first electrode.

[0109] Embodiment 14

[0110] A method for preparing an electrode loaded with an amorphous catalyst:

[0111] The difference between this embodiment and embodiment 1 is only in step (5), specifically:

[0112] The stress generated by mechanical impact during the cold spraying process is eliminated by low-temperature annealing heat treatment. The annealing heat treatment temperature is 200°C, the time is 0.4h, and the atmosphere is a nitrogen atmosphere. Thereafter, the aluminum element in the aluminum-magnesium alloy is removed by alkali leaching to obtain a nickel-cobalt amorphous electrode. The alkali solution required for the alkali leaching treatment is a 5wt% potassium hydroxide solution. The treatment temperature is 10°C and the treatment time is 30h. 5wt% potassium sodium tartrate is added to the solution as a corrosion inhibitor, and finally an electrode loaded with an amorphous catalyst is obtained.

[0113] Embodiment 15

[0114] A method for preparing an electrode loaded with an amorphous catalyst:

[0115] The difference between this embodiment and embodiment 1 is only in step (5), specifically:

[0116] The stress generated by mechanical impact during the cold spraying process is eliminated by low-temperature annealing heat treatment. The annealing heat treatment temperature is 400°C, the time is 6 hours, and the atmosphere is a nitrogen atmosphere. Thereafter, the aluminum element in the aluminum-magnesium alloy is removed by alkali leaching to obtain a nickel-cobalt amorphous electrode. The alkali solution required for the alkali leaching treatment is a 40wt% potassium hydroxide solution. The treatment temperature is 100°C, and the treatment time is 3 hours. 5wt% potassium sodium tartrate is added to the solution as a corrosion inhibitor, and finally an electrode loaded with an amorphous catalyst is obtained.

[0117] Example 16

[0118] A method for preparing an electrode loaded with an amorphous catalyst:

[0119] The only difference between this embodiment and embodiment 1 is that a 46-mesh twill woven nickel mesh is used instead of nickel felt as the metal nickel substrate.

[0120] Comparative Example 1

[0121] A method for preparing an electrode:

[0122] The only difference between this comparative example and Example 1 is that step (1) and step (2) are not performed, and instead the mixed amorphous powder is directly sprayed onto one side surface of the metal nickel substrate by high-pressure cold spraying, and then heat treated to obtain an electrode having only an amorphous catalyst layer.

[0123] Comparative Example 2

[0124] A method for preparing an electrode:

[0125] The only difference between this comparative example and Example 1 is that step (2) is not performed, and instead the mixed aluminum-magnesium powder is directly coated on one surface of the metal nickel substrate and sintered at 500°C to obtain an aluminum-magnesium alloy transition layer, and finally an electrode loaded with an amorphous catalyst is obtained.

[0126] That is, the alloy transition layer is not prepared by plasma spraying, but is prepared by sintering after coating.

[0127] Comparative Example 3

[0128] A method for preparing an electrode:

[0129] The only difference between this comparative example and Example 1 is that no cobalt chloride is added in step (3), that is, there is no second amorphous metal source in the amorphous metal source.

[0130] Comparative Example 4

[0131] A method for preparing an electrode:

[0132] The difference between this comparative example and Example 1 is that in step (3), the amount of cobalt chloride is changed to 75 g, and the amount of nickel chloride is changed to 25 g.

[0133] At this time, the weight ratio of the first amorphous metal source to the second amorphous metal source is 1:3.

[0134] Comparative Example 5

[0135] A method for preparing an electrode:

[0136] The only difference between this comparative example and Example 1 is that step (4) is not performed, and instead the mixed amorphous powder is directly coated on the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate, and sintered at 400°C to obtain an amorphous catalyst layer, and finally an electrode loaded with an amorphous catalyst is obtained.

[0137] That is, the amorphous catalyst layer is not prepared by cold spraying, but is prepared by coating and then sintering.

[0138] Comparative Example 6

[0139] A method for preparing an electrode:

[0140] The only difference between this comparative example and Example 1 is that step (5) is not performed, and the first electrode is directly used as the final electrode loaded with an amorphous catalyst.

[0141] Test Method

[0142] Alkaline water electrolysis system: Cut the electrodes obtained in each example and comparative example into a rectangular block with a length of 1.5 cm and a width of 1 cm, fix it with an electrode clamp and use it as a working electrode for oxygen evolution reaction (OER) in alkaline electrolyte. In the three-electrode test system, the platinum wire is the counter electrode, the mercury / mercuric oxide electrode is the reference electrode, and the effective area of ​​the working electrode immersed in the electrolyte is 1 cm 2 , 1 mol / L potassium hydroxide was selected as the electrolyte in the test system. The electrochemical data were tested by linear voltammetry and AC impedance method. The rate of linear voltammetry was 5 mV / s, the test potential of AC impedance was 1.53 V (vs. RHE), the AC amplitude was 10 mV, and the frequency range was 106 to 10 -1 Hz, each electrode is 100mA / cm 2 The overpotential under current density. The smaller its value, the faster the charge transfer between the electrode interface and the electrolyte, that is, it shows a higher oxygen evolution catalytic activity. 2 The electrode prepared by spraying on nickel foam was used as a control.

[0143] Anion exchange membrane water electrolysis system: The electrodes obtained in each embodiment and comparative example were used as self-supporting electrodes directly in the cathode and anode gas diffusion layers of anion exchange membrane (AEM) electrolyzer. AEM selected commercial membrane FAA-3-50. During the test, the electrode clamps of the electrochemical workstation were clamped on the positive and negative electrodes of the electrolyzer, 1M KOH solution was circulated at a flow rate of 100ml / min, the heating device was turned on, and the temperature was set to 60°C, and each sample reached 2.5A / cm in the water electrolysis test. 2 The cell voltage at the current density represents the hydrogen production voltage value of a single electrolysis unit when a certain current density is reached. Therefore, the lower the value, the lower the energy consumption under the current density and the higher the economic efficiency of the hydrogen production reaction. 2 The prepared membrane electrode was used as a control.

[0144] The above test results are shown in Table 1.

[0145] Table 1

[0146]

[0147]

[0148] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve a close combination between the amorphous catalyst and the electrode, and the obtained electrode loaded with the amorphous catalyst has excellent catalytic activity and stability, and exhibits high HER and OER catalytic activity in both alkaline water electrolysis system and AEM water electrolysis system.

[0149] Specifically, compared with Example 1: Example 2 has higher activity, which is attributed to the fact that the material will be converted into nickel-iron hydroxide active components in OER, which is more conducive to the OER reaction kinetics process than the nickel-cobalt catalytic system; Example 3 prepared a four-way catalyst, and the addition of more metal elements improved the long-range disorder of the material, the amorphous properties of the material were more significant, and the catalytic activity was higher; Example 4 synthesized a noble metal amorphous material based on noble metal salts, proving the scalability of the synthesis method, but the platinum-based catalyst has a higher hydrogen evolution activity and slightly worse performance in oxygen evolution; Example 5 is a four-way catalyst system, and its performance is better than that of Example 1, but slightly more iron is added, In OER, it will be converted into iron hydroxide oxide with poor conductivity, so the performance is slightly worse than that of Example 3; Example 6 increases the magnesium content in the aluminum-magnesium transition coating, but the corresponding reduction in the pore-forming aluminum content will cause a slight decrease in the porosity of the cost electrode coating, which will affect the mass transfer process in the electrochemical reaction; In Example 7, the aluminum content in the aluminum-magnesium transition coating is increased, and the increase in the pore-forming aluminum content will cause the strength of the porous structure of the coating to decrease, and the proportion of collapse or closure in the pore structure will increase, which will also affect the mass transfer process in the electrochemical reaction; In Example 8, low power is used for aluminum-magnesium alloy cladding, resulting in weak bonding between the coating and the substrate, and the catalyst is easy to fall off and is not attached to the substrate The electron transfer is limited, resulting in a decrease in performance; in Example 9, the coating is clad by high power and fast powder feeding, and the molten aluminum-magnesium alloy quickly fills the pore structure of the substrate, resulting in a reduction in the catalytic active area and obstruction of gas overflow, so the performance is greatly reduced; in Example 10, increasing the amount of sodium borohydride and extending the ball milling time will lead to an increase in the crystallinity of the multi-element transition metal catalyst, and a weakening of the amorphous characteristics, resulting in a decrease in performance; in Example 11, reducing the amount of sodium borohydride and extending the ball milling time will lead to incomplete reduction of the multi-element metal salt, and the structural integrity of the amorphous catalytic material finally formed is poor, so the performance is poor; in Example 12, the cold spraying pressure and temperature The cold spraying pressure and temperature are too high, resulting in weak bonding between the amorphous material and the aluminum-magnesium alloy coating, low structural strength of the amorphous coating, easy to fall off, and performance degradation; in Example 13, the cold spraying pressure and temperature are too high, the crystallinity of the amorphous material increases during the spraying process, and sintering agglomeration occurs in the coating, so the performance is significantly reduced; in Example 14, the thermal annealing temperature is insufficient and the potassium hydroxide concentration is too low, resulting in incomplete stress elimination and incomplete removal of the pore-forming agent aluminum, resulting in performance degradation; in Example 15, the annealing temperature is too high and the time is too long, resulting in an increase in the degree of crystallization of the material; in Example 16, after replacing the substrate with a twill woven nickel mesh, an amorphous coating with high activity can still be synthesized on the surface.

[0150] Compared with the above embodiments: in Example 1, when the low-melting-point aluminum-magnesium coating is not melt-coated on the surface of the substrate, the amorphous material fails to form a good bond with the substrate through cold spraying, and the coating easily falls off, resulting in a significant decrease in the catalytic performance; in Example 2, the aluminum-magnesium transition coating constructed by calcination has low strength with the substrate and fails to connect the amorphous coating and the substrate; in Example 3, no second metal source is added, so the electronic structure of cobalt and the degree of amorphization cannot be effectively regulated, and the catalytic performance is low; in Example 4, the atomic ratio of different metals deviates from the preferred ratio, resulting in a decrease in performance; in Example 5, calcination increases the overall crystallinity of the amorphous material, weakens the catalytic properties of the amorphous material, and thus reduces the catalytic activity; in Example 6, the aluminum-magnesium alloy coating alone does not have OER catalytic performance and cannot be used directly as an electrode.

[0151] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0152] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an electrode loaded with an amorphous catalyst, characterized in that: include: Step S1, performing a first mixing of aluminum metal powder and magnesium metal powder to obtain a mixed aluminum-magnesium powder; Step S2, spraying the mixed aluminum-magnesium powder onto at least one side of the surface of the metal nickel substrate by vacuum plasma spraying to obtain the metal nickel substrate loaded with an aluminum-magnesium alloy transition layer; Step S3, performing a second mixing of the amorphous metal source and the auxiliary agent to obtain a mixed amorphous powder; Step S4, spraying the mixed amorphous powder onto the surface of the aluminum-magnesium alloy transition layer away from the metal nickel substrate by cold spraying to obtain an amorphous catalyst layer, and then obtaining a first electrode; Step S5, sequentially performing heat treatment and alkaline leaching on the first electrode to obtain the electrode loaded with the amorphous catalyst; The amorphous metal source includes a first amorphous metal source and a second amorphous metal source, and a weight ratio of the first amorphous metal source to the second amorphous metal source is 1:(1-2.5); The first amorphous metal source is a nickel source, and the second amorphous source is one or more of a noble metal source and / or a transition metal source other than the nickel source.

2. The method for preparing an electrode loaded with an amorphous catalyst according to claim 1, characterized in that: The second amorphous source is one or more metal sources with atomic numbers of 22 to 30 except the nickel source; Preferably, the second amorphous metal source is selected from one or more of a cobalt metal source, an iron metal source and a copper metal source; More preferably, the second amorphous metal source is a cobalt metal source, an iron metal source and a copper metal source, and the weight ratio of the cobalt metal source, the iron metal source and the copper metal source is 1:(0.4-0.6):1; Further preferably, the first amorphous metal source and the second amorphous metal source are each independently in the form of one or more of nitrate, sulfate, acetate, acetylacetonate and chloride.

3. The method for preparing an electrode loaded with an amorphous catalyst according to claim 1 or 2, characterized in that: In step S1, The weight ratio of the aluminum metal powder to the magnesium metal powder is 1:(0.1-10), preferably 1:(1-2); Preferably, the mesh sizes of the aluminum metal powder and the magnesium metal powder are independently 100 mesh to 500 mesh; More preferably, the first mixing method is ball milling, and the rotation speed of the ball milling is 150r / min to 500r / min, the time is 0.5h to 10h, and the ball milling beads are zircon beads of 10mm to 30mm; Further preferably, the dispersion liquid used for the ball milling is ethanol, and the ratio of the weight of the ethanol to the sum of the weight of the aluminum metal powder and the magnesium metal powder is 1:(6-12).

4. The method for preparing an electrode loaded with an amorphous catalyst according to any one of claims 1 to 3, characterized in that: In step S2, The power of the vacuum plasma spraying is 20 kW to 25 kW, the powder feeding rate is 10 g / min to 100 g / min, the distance between the nozzle and the metal nickel substrate is 25 cm to 80 cm, and the movement rate of the spray gun is 50 cm / s to 80 cm / s; Preferably, in the vacuum plasma spraying, the process gas for generating plasma is a H2 / Ar mixed gas, and the total flow rate of the H2 / Ar mixed gas is 8L / min to 15L / min; More preferably, in the H2 / Ar mixed gas, the volume ratio of the H2 to the Ar is 1:(2-10).

5. The method for preparing an electrode loaded with an amorphous catalyst according to any one of claims 1 to 3, characterized in that: In step S3, The molar ratio of the amorphous metal source to the auxiliary agent is (0.2-10):1, preferably (2.0-6.0):1; Preferably, the auxiliary agent is selected from one or more of sodium borohydride, thiourea and sodium hypophosphite, preferably sodium borohydride; More preferably, the second mixing method is ball milling, and the rotation speed of the ball milling is 150r / min to 500r / min, the time is 0.5h to 10h, and the ball milling beads are zircon beads of 10mm to 30mm; Further preferably, the dispersion liquid used for the ball milling is ethanol, and the ratio of the weight of the ethanol to the sum of the weight of the amorphous metal source and the auxiliary agent is 1:(4-8).

6. The method for preparing an electrode loaded with an amorphous catalyst according to any one of claims 1 to 5, characterized in that: In step S4, The cold spraying pressure is 1MPa-10MPa, the temperature is 400°C-600°C, the distance between the nozzle and the aluminum-magnesium alloy transition layer is 10cm-60cm, the powder feeding rate is 10g / min-100g / min, and the spray gun moving rate is 20cm / s-60cm / s; Preferably, the propelling gas used for the cold spraying is a N2 / He mixed gas, and in the N2 / He mixed gas, the volume ratio of the N2 to the He is 1:(0.1-10), more preferably 1:(4-5).

7. The method for preparing an electrode loaded with an amorphous catalyst according to any one of claims 1 to 6, characterized in that: In step S5, The heat treatment temperature is 250°C to 350°C, the time is 0.5 to 5 hours, and the atmosphere used is selected from one or more of air atmosphere, vacuum atmosphere, nitrogen atmosphere, argon atmosphere, hydrogen atmosphere and helium atmosphere; and / or, The mass concentration of the alkali solution used for the alkali leaching is 10wt% to 30wt%, and the alkali leaching is carried out at 25°C to 80°C for 6h to 24h.

8. An electrode loaded with an amorphous catalyst, comprising a metal nickel substrate, characterized in that: The electrode loaded with an amorphous catalyst is prepared by the method for preparing an electrode loaded with an amorphous catalyst according to any one of claims 1 to 7.

9. The electrode loaded with an amorphous catalyst according to claim 8, characterized in that: The electrode loaded with an amorphous catalyst further comprises an alloy transition layer and an amorphous catalyst layer loaded on at least one side surface of the metal nickel substrate, and the alloy transition layer is arranged in contact with the metal nickel substrate, and the amorphous catalyst layer is arranged on a side surface of the alloy transition layer away from the metal nickel substrate; Preferably, the thickness of the amorphous catalyst layer is 10 μm to 150 μm, more preferably 40 μm to 50 μm.

10. Use of the electrode loaded with an amorphous catalyst as claimed in claim 8 or 9 as an electrode in a water electrolysis hydrogen production system, characterized in that: The water electrolysis hydrogen production system is an alkaline water electrolysis system or an anion exchange membrane water electrolysis system; Preferably, the water electrolysis hydrogen production system is the alkaline water electrolysis system, and the electrode loaded with the amorphous catalyst serves as an oxygen evolution working electrode and / or a hydrogen evolution working electrode in the alkaline water electrolysis system; and / or, The water electrolysis hydrogen production system is the anion exchange membrane water electrolysis system, and the electrode loaded with an amorphous catalyst serves as a self-supporting oxygen evolution electrode and / or a self-supporting hydrogen evolution electrode in the anion exchange membrane water electrolysis system.

Citation Information

Patent Citations

  • Preparation method of alkaline water electrolysis electrode, electrode and water electrolysis equipment

    CN116200769A

  • Cathode for hydrogen production through alkaline water electrolysis and preparation method and application thereof

    CN116288509A

  • Porous catalytic electrode and preparation method and application thereof

    CN117867433A

Cited By

  • Ordered functionalized oxygen evolution electrode and preparation method thereof

    CN121674997A